2020
DOI: 10.1002/kin.21429
|View full text |Cite
|
Sign up to set email alerts
|

Isomer‐dependent reaction mechanisms of cyclic ether intermediates: cis‐2,3‐dimethyloxirane and trans‐2,3‐dimethyloxirane

Abstract: Oxiranes are a class of cyclic ethers formed in abundance during lowtemperature combustion of hydrocarbons and biofuels, either via chainpropagating steps that occur from unimolecular decomposition of βhydroperoxyalkyl radicals (β-QOOH) or from reactions of HOȮ with alkenes. The cis-and trans-isomers of 2,3-dimethyloxirane are intermediates of n-butane oxidation, and while rate coefficients for β-QOOH → 2,3-dimethyloxirane +ȮH are reported extensively, subsequent reaction mechanisms of the cyclic ethers are no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(44 citation statements)
references
References 83 publications
(166 reference statements)
1
43
0
Order By: Relevance
“…Dissociative ionization has been observed previously for ethyl peroxy and propyl peroxy, and stable parent cations have been reported for methyl peroxy and alkenyl peroxy . However, the absolute PI cross section of ROO we report here is only the third such determination to date, building on the recent PI spectra of methyl peroxy and ethoxyethyl peroxy from our group.…”
Section: Results and Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Dissociative ionization has been observed previously for ethyl peroxy and propyl peroxy, and stable parent cations have been reported for methyl peroxy and alkenyl peroxy . However, the absolute PI cross section of ROO we report here is only the third such determination to date, building on the recent PI spectra of methyl peroxy and ethoxyethyl peroxy from our group.…”
Section: Results and Discussionsupporting
confidence: 71%
“…The high-pressure experiments, conducted with ∼50–500 higher oxygen partial pressure than at 10 Torr, lead to much higher rate coefficients for O 2 addition and much more efficient collisional relaxation of chemically activated radicals. Our previous work on alkane, ether, and ketone oxidation revealed that high- P , high-oxygen conditions in the HPR enhance second-O 2 addition relative to the LPR. ,, We therefore assigned the m / z = 67, 84, 100, and 116 peaks at 3000 and 7500 Torr to species formed by γ-QOOH + O 2 , as shown in Figure . In addition, the time dependence of m / z = 57 and 82 peaks (marked with asterisks in Figure ) suggests that they are also likely due to DI fragments of second-O 2 addition products; however, we could not definitively assign them.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Our recent study on the reactivity of a series of epoxides towards chlorine atoms in gas phase using quantum mechanical calculations agrees with these findings. As we discussed in Tovar et al (2021), if we consider the case of cisand trans-epoxybutane, when the compound has lost one H of the CH 3 group, it becomes trigonally (sp 2 ) hybridized, facilitating the possible formation of a double bond with the singly occupied p-orbital after abstraction of H. This effect could explain the formation of acrolein from Cl-initiated oxidation of both cis-2,3dimethyloxirane and trans-2,3-dimethyloxirane with yields of 36.49 ± 0.55 and 49.08 ± 1.29 at 650 and 800 K, respectively, in the work presented by Doner et al (2021). The formation of the vinyl oxirane from β hydrogen abstraction and the subsequent formation of the keto hydro peroxy radical reported by Christianson et al (2021) for the oxidation of 1,2-epoxybutane also confirm this theory.…”
Section: Pseudo-ethylenic Character In the Epoxy Ring As The Main Fac...mentioning
confidence: 81%
“…This is largely due to the lack of insight on the consumption reactions, which include site-specific H-abstraction reactions, the ring-opening of cyclic ether radicals, and the reactions of cyclic ether radicals with O 2 . The latter can traverse QOOH-mediated pathways 17–19 in a manner similar to hydrocarbons but can have more complicated chemical behavior as well, due to the C–O bonds in the molecular structure. It has been shown before that the unimolecular reactions of cyclic ether peroxy radicals can lead to ketohydroperoxide-type radicals 17,18 and dicarbonyls.…”
Section: Introductionmentioning
confidence: 99%